Affiliate training is a student of a pedagogical university in the independent study of physics (Pedagogy of Higher and Secondary Education, 2012)
Polovina G. P. Affiliate training is a student of a pedagogical university in the independent study of physics.In this work one of motivation increase approaches of training at research of the phenomenon with caused interest is considered. To the solution of this problem the teachers and professors of higher educational institution and also the pupil and the student of pedagogical institution are involved.
Keywords: partner training; independent activity; research work; creative thinking